CXCR4 and Axillary Lymph Nodes: Review of a Potential Biomarker for Breast Cancer Metastasis - David Hiller; Quyen D. Chu (International Journal of Breast Cancer)
CXCR4 is a 7-transmembrane G-protein chemokine receptor that allows for migration of hematopoietic cells from the bone marrow to the peripheral lymph nodes. Research has shown CXCR4 to be implicated in the invasion and metastasis of several cancers, including carcinoma of the breast. CXCL12 is the ligand for CXCR4 and is highly expressed in areas common for breast cancer metastasis, including the axillary lymph nodes. Axillary lymph nodes positive for breast carcinoma have been an important component of breast cancer diagnosis, treatment, and subsequent research. The goal of this paper is to analyze the literature that has explained the pathways from CXCR4 expression to breast cancer metastasis of the lymph nodes and the prognostic and/or predictive implications of lymph node metastases in the presence of elevated CXCR4.